Amid Covid-19: The Rise of Gaming Addiction - Nur Faizah Abdul Kahar; Farhana Sabri; Azreena Abu Bakar; Hanifah Abdul Hamid; Nuradli Ridzwan Shah Mohd Dali (Human Resource Management Academic Research Society, 2024)
Indexed by ERA